The Prototype Sistem Informasi Kepegawaian Berbasis Web - Mardiana; Syafwan Hilman; Roynaldi Rahman (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2020)
Jasa Raharja (Persero) is a State-Owned Enterprise that specializes in managing road accident insurance. PT. Jasa Raharja always serves the community very well in terms of social insurance for public transport and road users. Human Resources is a major concern for company management in terms of achieving goals and the totality of individual work and company performance. Human resource data management need to be done properly and systematically so that every personnel administration activity becomes more effective and efficient. In this research the staffing information system that was built could process employee data, salaries, ranks, transfers, paid leave and training. This study uses the prototype method as a system development method with DFD and ERD modeling. The purpose of this research is to produce a prototype of a web-based staffing information system at PT. Jasa Raharja (Persero).